A comparative study of the effects of three Moringa species on obesity- induced oxidative stress state in liver tissue - ELHAM M.YOUSSEF ELABD,; ZAHRAN, H. A,; ABOELFETOH M. ABDALLA, (International Journal of Pharma and Bio Sciences, 2017)
Excessive consumption of a diet rich in fat leads to obesity and progressive forms of liver abnormalities due to oxidative stress. In the present study, antiobesity and antioxidant activity of oil extracted from seeds of three Moringa species, Moringa peregrina, Moringa stenopetala, and Moringa oleifera were evaluated and confirmed with histopathological examination of rat liver tissues. Results showed that administration of high fat diet induced liver damage, increased body weight, liver biomarkers, lipid peroxide levels while reduced antioxidant enzyme levels. Treatment with the three types of Moringa oil resulted in a significant (ð‘ƒ<0.05) change in body weight, a significant (ð‘ƒ<0.05) increase in antioxidant enzymes and a significant decrease in liver biomarker levels. However, histopathological examination confirmed that M. stenopetala significantly showed hepatocyte restoration. In conclusion, Moringa peregrina, Moringa stenopetala, and Moringa oleifera have antiobesity and antioxidant activity, however, M.stenopetala has served as the most effective type in reduction adiposity and hepatic steatosis.